1977
DOI: 10.1111/j.1751-0813.1977.tb00134.x
|View full text |Cite
|
Sign up to set email alerts
|

HISTOPHILUS OVIS INFECTION IN SHEEP IN WESTERN VICTORIA

Abstract: Organisms resembling Histophilus ovis were isolated from sheep in Western Victoria in association with synovitis, septicaemia and/or abscessation in 2 to 8 week old lambs. Histopathological lesions in these lambs were indicative of bacterial embolism with thrombosis. Similar organisms were also isolated from sheep in 2 flocks with a high neonatal mortality rate. These isolations were from vaginal swabs from the ewes, placentas and from one lamb which had meningitis, ependymitis, choroid plexitis, hepatic necro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
2

Year Published

1982
1982
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 10 publications
1
15
0
2
Order By: Relevance
“…Phenotypically similar bacteria had previously been isolated from sheep; for example, an organism named 'Histophilus ovis' had already been isolated (Mitchell, 1925), but this isolate is no longer available. In 1956, 'Histophilus ovis' was isolated from mastitis in sheep (Roberts, 1956) and has since been isolated from ovine septicaemia, synovitis and epididymitis and from ovine vaginas (Rahaley & White, 1977;Rahaley, 1978). In 1958, a bacterium was isolated from lambs with septicaemia in Australia and designated 'Haemophilus agni' (Kennedy et al, 1958).…”
Section: Introductionmentioning
confidence: 99%
“…Phenotypically similar bacteria had previously been isolated from sheep; for example, an organism named 'Histophilus ovis' had already been isolated (Mitchell, 1925), but this isolate is no longer available. In 1956, 'Histophilus ovis' was isolated from mastitis in sheep (Roberts, 1956) and has since been isolated from ovine septicaemia, synovitis and epididymitis and from ovine vaginas (Rahaley & White, 1977;Rahaley, 1978). In 1958, a bacterium was isolated from lambs with septicaemia in Australia and designated 'Haemophilus agni' (Kennedy et al, 1958).…”
Section: Introductionmentioning
confidence: 99%
“…H. somni is a fastidious and slow-growing organism with low biochemical activity. H. somni is associated with a variety of conditions such as septicaemia, myocarditis, arthritis, pyaemia, mastitis, metritis, abortion, neonatal mortality, decreased fertility in ewes and rams, epididymo-orchitis, pneumo nia and thrombotic meningoencephalitis (Robert, 1956;Rahaley and White, 1977;Rahaley, 1978a;Webb, 1983b;Harris and Janzen, 1989;Philbey et al 1991;Cassidy et al, 1997). H. somni has aIso been iso lated from the vagina and vaginal fluids of c1inicaUy normal ewes (Rahaley, 1978b;Higgins et al, 1981;Harris and Janzen, 1989) and it has been suggested that the genital (Webb, 1983b) and respiratory (Philbey et al, 1991) tracts are the natural habitats of H. somni.…”
Section: Histophilus Somnimentioning
confidence: 99%
“…Among the nearly 500 strains which have been characterized by differential tests and reported in the literature (1,4,5,7,10,14,17,18,(21)(22)(23)(24)(25)28), variability has been noted in practically all of the key biochemical and cultural features that have been described. These include oxidase (28) and catalase tests (1, 5 ) , raised carbon dioxide requirement (1,26), hemolytic activity (5,22), indole production (1,5,14,18,20,25), decarboxylase tests (7,21), reduction of nitrate (9, esculin hydrolysis (21,22), and acid production from carbohydrates (24).…”
Section: Discussionmentioning
confidence: 99%
“…These include oxidase (28) and catalase tests (1, 5 ) , raised carbon dioxide requirement (1,26), hemolytic activity (5,22), indole production (1,5,14,18,20,25), decarboxylase tests (7,21), reduction of nitrate (9, esculin hydrolysis (21,22), and acid production from carbohydrates (24). These variations often appear to be related to strain origin by host species.…”
Section: Discussionmentioning
confidence: 99%